2019
DOI: 10.1136/jnnp-2019-abn.75
|View full text |Cite
|
Sign up to set email alerts
|

FM2-2 Exploratory analysis whether wearable sensor data can correlate with aspects of non-motor symptoms in parkinson’s: a real life study with the parkinson’s kinetigraphTM

Abstract: ObjectivesTo determine the association between the range and nature of non-motor symptoms (NMS) in people with Parkinson’s (PwP) and validated Parkinson’s KinetigraphTM (PKG) outcome measures.DesignCross-sectional retrospective study of participants enrolled in the Non-motor Longitudinal International Study (NILS, UKCRN No: 10084) at King’s College Hospital, London.Subjects108 PwP with a PKG recording within 4 months of a NILS assessment were included in the analysis.MethodsPKG is a validated accelerometery-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Illustrating this are data from an unselected cohort of 200 PD patients being recruited to an international wearable sensor registry study showing that significant dyskinesia is observed among only 18.5% of the moderate‐ to advanced‐stage PD population referred to King's College Hospital (London), a major academic teaching hospital. This is in line with the studies by Scott and colleagues and Bjornestad and colleagues and might even be an overestimation given that our center is a reference center for advanced therapies . An additional factor to consider also is the under‐recognized phenomenon of “levodopaphobia” where patients intentionally avoid or delay taking clinically effective doses of l ‐dopa for the fear of dyskinesia .…”
supporting
confidence: 79%
“…Illustrating this are data from an unselected cohort of 200 PD patients being recruited to an international wearable sensor registry study showing that significant dyskinesia is observed among only 18.5% of the moderate‐ to advanced‐stage PD population referred to King's College Hospital (London), a major academic teaching hospital. This is in line with the studies by Scott and colleagues and Bjornestad and colleagues and might even be an overestimation given that our center is a reference center for advanced therapies . An additional factor to consider also is the under‐recognized phenomenon of “levodopaphobia” where patients intentionally avoid or delay taking clinically effective doses of l ‐dopa for the fear of dyskinesia .…”
supporting
confidence: 79%